Third World countries : struggle for new economic order - Dutta, Kalyan (New Delhi : Sterling, 1979)
This book examines the economic backwardness of the countries of Asia, Africa and Latin America. The exploitation of these countries by the industrialized countries of Europe and United States through trade and investment and the quest for the Third World Countries to lift their economy through improvement on the per capital national income in an unjust economic order.
usc 11/04/2018
Loans
Keywords: International economic relations; Developing countries